PERANAN BIDANG OLAHRAGA DISPORA PROVINSI RIAU DALAM MENDUKUNG PEMBINAAN ATLIT PELAJAR DI PROVINSI RIAU TAHUN 2012 - ", Rahmadani; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research is motivated by a not optimal and uneven development of studentathletes in Riau Province. This study aims to describe the role of Head of Sport insupporting students in Riau Province in 2012, and to determine the factors thatinfluence the performance of the Head of Sport in improving student achievementand well-being of athletes in Riau Province in 2012. Sites for this research RiauProvince is located Dispora housed in Pekanbaru. Subjects were 9 people in theDispora informants related Riau province in the field of sports. Engineering major orprimary data collection using interviews. Results reveal that the Dispora's role insupporting the development of student athletes is to hold a sporting event. In addition,the implementation of PPLP to support student athletes achievements. According tothe athletes, facilities and infrastructure provided by the Dispora during the coachingprocess is quite adequate. There are no significant obstacles during the developmentprocess. The problem that occurs is the lack of supervision by the Head of exercise oncation-cation of the sport in running sports program within budget and the programsthat have been created.Keywords : Role, Supporting Student Athlete, Running Sports Program